Growth performance and nutrient composition of black soldier fly larvae reared on solid-state fermentation substrates with various white rot fungi (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fitriana EL, Jayanegara A, Astuti DA, Laconi EB. 2022. Growth performance and nutrient composition of black soldier fly larvae reared on solid-state fermentation substrates with various white rot fungi. Biodiversitas 23: 4894-4905. This study examines agricultural byproducts fermented with various rot fungi as a substrate of black soldier fly larvae. The experiment used a three-way randomized design with four replications. The first factor was substrate (cacao pod husk and oil palm frond), the second factor was fungi (Phanerochaete chrysosporium, Trametes versicolor, and Pleurotus sajor-caju), and the third factor was environment condition (light and without light). Approximately 1200 of 7-day-old larvae were added to 600 g substrate treatment. The results showed that the solid-state fermentation substrates had the highest waste reduction parameters and level of consumption. Larvae in the experiment had a crude protein level of 38.84-58.88% of dry matter. Glutamic acid is the most abundant non-essential amino acid in larvae, while leucine is the most abundant essential amino acid. Solid-state fermentation substrate could improve the fatty acid profile quality of larvae in relation to high linoleic acid, polyunsaturated fatty acid, and unsaturated fatty acid percentages, especially CPH-pc substrate. The use of solid-state fermentation in larvae rearing decreased lignin in the cacao pod husk substrate. In conclusion, cacao pod husk substrate solid-state fermented with white rot fungi is not supported the optimum growth performance of BSFL but increases fatty acid profile quality.
Keywords: Agricultural byproduct, feed, fiber fraction, insect